Low-cost group-based identity security authentication protocol for NB-IoT nodes - Xiangmao CHANG; Jun ZHAN; Zhiwei WANG (Tongxin xuebao)
To address the problem of huge number of signaling requests when large-scale devices request authentication in NB-IoT network， a low-cost group identity security authentication protocol based on Schnorr aggregate signature and Chinese reminder theorem was proposed.The protocol enabled the server to perform one-time authentication of the device group with a size-fixed group authentication request， which effectively reduced the bandwidth consumption of the authentication request.The protocol used a session key distribution mechanism based on the Chinese remaining theorem， allowing the server to complete the distribution of keys for each device in the group by size-fixed message.The results of security verification and the performance analysis show that the proposed protocol has reliable safety and superior performance in terms of transmission load and bandwidth consumption.